Does improving Public Transport decrease Car Ownership? Evidence from the Copenhagen Metropolitan Area - Ismir Mulalic; Ninette Pilegaard; Jan Rouwendal (Tinbergen Institute, 2015)
Car ownership is lower in urban areas, which is probably related to the availability of better public transport. Better public transport thus may offer the possibility to relieve the many problems (congestion, health, and parking) associated with the presence of cars in urban areas. To investigate this issue, we develop and estimate a model for the simultaneous choice of a residential area and car ownership. The model is estimated on Danish register data for single-earner and dual-earners households in the greater Copenhagen metropolitan area. We pay special attention to accessibility of the metro network which offers particularly high quality public transport. Simulations based on the estimated model show that for the greater Copenhagen area a planned extension of the metro network decreases car ownership by 2-3%. Our results suggest also a substantial increase in t he interest for living in areas close to the metro network, that affects the demographic composition of neighbourhoods.
Keywords: R4; R1; D1; 330; car ownership; public transport; residential sorting